Vulnerability, extremism, and schooling: restorative practices, policy enactment, and managing risk - Stahl, Garth (Lexington Books, 2024)
"Drawing on theories of affective governance, securitization, surveillance, and neoliberal risk management, this book analyzes efforts by educational policymakers to combat susceptibility to extremism within disadvantaged communities"--